Alteration of moving bed sequencing batch reactor operational strategies for the enhancement of nitrogen removal from stabilized landfill leachate - Tan, K.-C. (Taylor and Francis Inc., 2016)
Stabilized landfill leachate is well known to contain high concentration of nitrogen particularly in the ammonium nitrogen (Formula presented.) -N form. Also considering of high toxicity of non-biodegradable and low proportion of biodegradable compounds in stabilized landfill leachate, the conventional biological treatment of nitrogen is usually inefficient. As such, the quest of this study was to revise the operational strategies of bioreactor, i.e. moving bed sequencing batch reactor (MBSBR), for the enhancement of nitrogen removal from stabilized landfill leachate. The performance of MBSBRs packed with 8 (v/v) of polyurethane (PU) cubes and polyethylene (PE) rings, respectively, in removing nitrogen from a combined stabilized landfill leachate and domestic wastewater in increasing leachate volumetric ratio under various operational strategies was investigated. On increasing the leachate volumetric ratio to 14, the performance of both MBSBRs in (Formula presented.) -N removal was comparable under the continuous aeration strategy. When the aeration strategy was changed to intermittent aeration (IA), the MBSBR with PU media achieved a higher (Formula presented.) -N removal rate, while the MBSBR with PE media failed to remove (Formula presented.) -N completely. For the MBSBR with PU media, the adoption of IA coupled with step feeding strategy had yielded a removal efficiency of 80 for total nitrogen in comparison to 64 if only IA strategy was adopted at the leachate volumetric ratio of 14. Nevertheless, further increase in leachate volumetric ratio to 20 had led to the accumulation of (Formula presented.) -N in the effluent of MBSBR under IA-SF strategy. At this stage, the MBSBR operated with IA strategy could still remove (Formula presented.) -N completely. Thus, the IA-MBSBR with PU media is the preferred operational strategy for nitrogen removal at higher leachate volumetric ratio. Â© 2015 Balaban Desalination Publications. All rights reserved.